MODIFIKASI SEDERHANA DARI VARIAN METODE NEWTON UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Putra, Supriadi (Edu Research, 2013)
This article discusses a simple modification of the variants of Newton's method for solving nonlinear equations. Jain (2013) combines the use of theSecant method with Trapezoidal Newton's method developed by Weerakon and Fernando (2000) and produces new combination Secant-Trapezoid Newton method that has fourth-order convergence. Using Jain's idea, the authors combine the use of the Secant method with two other variants of Newton's methoddeveloped by Ozban (2004), namely Arithmetic and Harmonic Newton. It turnsout that both the new combinations are has fourth-order convergence. Numericalcalculation with several examples of nonlinear equations is used to show that boththe new combinations method are comparable with other fourth-order methods.